2022
DOI: 10.1021/acs.jmedchem.2c00347
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective SERCA2a Activators: Preclinical Development of a Congeneric Group of First-in-Class Drug Leads against Heart Failure

Abstract: The stimulation of sarcoplasmic reticulum calcium ATPase SERCA2a emerged as a novel therapeutic strategy to efficiently improve overall cardiac function in heart failure (HF) with reduced arrhythmogenic risk. Istaroxime is a clinical-phase IIb compound with a double mechanism of action, Na + /K + ATPase inhibition and SERCA2a stimulation. Starting from the observation that istaroxime metabolite PST3093 does not inhibit Na + /K + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Of all these SERCA2a activators only istaroxime, a known Na + /K + transporting ATPase inhibitor as well as an inotropic/lusitropic agent acting to enhance SERCA2a activity, has been in phase IIb clinical trials for treatment of heart failure 45,46 . However, because of its unsuitability for human usage (poor gastrointestinal absorption, high clearance rate, and extensive metabolic transformation) 46 , istaroxime derivatives were designed from QSAR studies and a new promising class of SERCA2a activators has been identi ed 47,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Of all these SERCA2a activators only istaroxime, a known Na + /K + transporting ATPase inhibitor as well as an inotropic/lusitropic agent acting to enhance SERCA2a activity, has been in phase IIb clinical trials for treatment of heart failure 45,46 . However, because of its unsuitability for human usage (poor gastrointestinal absorption, high clearance rate, and extensive metabolic transformation) 46 , istaroxime derivatives were designed from QSAR studies and a new promising class of SERCA2a activators has been identi ed 47,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Of all these SERCA2a activators only istaroxime, a known Na + /K + transporting ATPase inhibitor as well as an inotropic/lusitropic agent acting to enhance SERCA2a activity, has been in phase IIb clinical trials for treatment of heart failure 45,46 . However, because of its unsuitability for human usage (poor gastrointestinal absorption, high clearance rate, and extensive metabolic transformation) 46 , istaroxime derivatives were designed from QSAR studies and a new promising class of SERCA2a activators has been identified 47,48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The enhancement of SR calcium load can be achieved by SERCA2a overexpression or by modification of signaling cascades that regulate SERCA2a at multiple levels, for example, via displacement or attenuating the inhibitory effect of the small endogenous protein phospholamban (PLB). , Recently, Luraghi et al reported on selective SERCA2a activators, derivatives of istaroxime metabolite, with unknown mechanism of action . There are published data on the N -aryl- N -alkyl-thiophene-2-carboxamide compound, which increases endoplasmic reticulum Ca 2+ load by enhancing SERCA2a-mediated Ca 2+ transport .…”
Section: Introductionmentioning
confidence: 99%